The Effect of Lifestyle on Pain Intensity in Knee Osteoarthritis Patients - Rusul Sheet Ahmad, Bashar Jassim Al-Jwary (Pakistan Journal of Medical & Health Sciences, 2023)
Background & Objectives: Knee osteoarthritis (OA) is a degenerative condition that damages the cartilage in the knee joint. The cartilage is a soft, rubbery tissue that acts as a joint cushion and friction reducer. As the joint’s cartilage diminishes, the bones rub against one another, resulting in pain, stiffness, and less mobility. Knee OA is a painful disorder that progresses with time and affects the whole knee joint, leading to varying pain intensity, stiffness, and swelling in the knee. It can also lead to disability, and Lifestyle factors were found to be related to knee OA. This study’s aim was to evaluate how lifestyle choices affected knee OA in patients visiting hospitals in Mosul, Iraq. The specific objectives of the study were to:1. Evaluate the socio-demographic characteristics for knee OA patients. To identify the lifestyle factors for patients with knee OA. To assess the effect of lifestyle on the pain intensity of knee OA. Methods: A cross-sectional study design was adopted for the period extended from the 1st of December 2022, to the 20th of July 2023. It included 500 knee osteoarthritis patients collected from consulting clinics in four teaching hospitals in Mosul, Iraq, by using a developed interviewing and self-admission questionnaire that assessed sociodemographic characteristics, health history, lifestyle factors, and the pain intensity on knee OA patients. Results: The mean age of patients (59.4) The majority of the participants were female (83.4%). (74.6%) of the sample were housewives, (75.4%) lived in urban. The most common risk factors for knee OA were obesity (27.2%), and family history (47.4%). (90.8%) of the patients had low education level. 37.2% of them at severe levels of constant pain intense. 28.6% of them at moderate levels of intermittent pain. Most of patients have a sedentary lifestyle. There are significant association between lifestyle domains with joint pain intensity. Lifestyle domains, except health self-responsibility and nutrition, significantly impact constant pain in knee and Health self-responsibility is associated with intermittent pain. Conclusion: Certain demographic and socio-demographic factors, such as age, gender, education, residency, occupation, BMI, previous knee injuries, and family history, had a significant association with knee osteoarthritis patients. This study has shown that lifestyle factors play a role in the pain intensity of knee OA. Lifestyle factors, such as physical activity, stress management, and enough sleep, have been shown to be effective in managing joint pain.. The findings can suggest that modification of lifestyle may be a protective against knee OA. Participants who reported being more physically active, eating a healthier diet, and maintaining a healthy weight were less likely to have knee pain. Keyword: Knee Osteoarthritis, Life-Style, Factor